The Impact of Capacity to Change and Change Leadership on Organizational Change Process - Ramona (MIHAI) PETRESCU (Revista de Management Comparat International)
Nowadays, change and how to lead it successfully has become the foremost topic on the minds of organizational leaders. And for good reasons: change is happening everywhere; its speed and complexity are increasing; and the future success of our organizations depends on how successful leaders are at leading that change. In today’s marketplace, change is a requirement for continued success, and competent change leadership is a most coveted executive skill.